Interface Design Enabling Stable Polymer/Thiophosphate Electrolyte Separators for Dendrite-Free Lithium Metal Batteries - Huo, Hanyu; Jiang, Ming; Mogwitz, Boris; Sann, Joachim; Yusim, Yuriy; Zuo, Tong-Tong; Moryson, Yannik; Minnmann, Philip; Richter, Felix H.; Veer Singh, Chandra; Janek, Jürgen; Justus Liebig University Giessen (My University, 2023)
Organic/inorganic interfaces greatly affect Li+ transport in composite solid electrolytes (SEs), while SE/electrode interfacial stability plays a critical role in the cycling performance of solid-state batteries (SSBs). However, incomplete understanding of interfacial (in)stability hinders the practical application of composite SEs in SSBs. Herein, chemical degradation between Li6PS5Cl (LPSCl) and poly(ethylene glycol) (PEG) is revealed. The high polarity of PEG changes the electronic state and structural bonding of the PS43− tetrahedra, thus triggering a series of side reactions. A substituted terminal group of PEG not only stabilizes the inner interfaces but also extends the electrochemical window of the composite SE. Moreover, a LiF-rich layer can effectively prevent side reactions at the Li/SE interface. The results provide insights into the chemical stability of polymer/sulfide composites and demonstrate an interface design to achieve dendrite-free lithium metal batteries.
Keywords: ddc:540